The TexOx Survey of Radio-Selected Galaxy Clusters - Croft, S; Rawlings, S; Hill, G; Gay, P; Tufts, JR (2001)
We present some initial results from the TexOx (Texas-Oxford) Cluster (TOC) survey - a new method of selecting distant galaxy clusters. The cosmic evolution of the radio source population suggests that some massive clusters at high redshift will contain several radio-loud AGN. We searched for extreme over-densities at ~mJy levels in 7' x 7' boxes within the NVSS radio catalogue, covering a large (~1100 square degree) sky area. We have acquired optical images for ~130 cluster candidates, and followed up a subset of these with the VLA, and with Calar Alto near-IR imaging. Ryle Telescope observations have yielded at least one Sunyaev-Zel'dovich (SZ) detection of a massive z~1 system. Spectroscopic follow-up with 8-m class telescopes is in progress.